Cross-Pollination Produces Arabica Coffee Beans with Higher Caffeine and Lower Fatty Acid - Dian Anggria Sari; Ramadhani Eka Putra (Biotropika: Journal of Tropical Biology, 2021)
Studies showed that cross-pollination also affect fruits and green bean coffee quantity and quality yet study on this subject in Indonesia rarely found. This study focused on assessing the pollination effect of fruit quality and beans in terms of size, weight, physical defect, and content of caffeine and fatty acid. During this study, Tetragonula laeviceps, indigenous stingless bees, were applied as a pollination agent to be compared to open pollination. The result showed that open pollination produced bigger beans (16.73abÂ±1.57 X 14.66aÂ±1.48 mm) with higher caffeine (18.22%) and lower fatty acid (41,86%), while application of T. laeviceps produced slightly heavier beans (0.22 gram). Besides producing higher caffeine and lower fatty acid, cross-pollination services mainly required wild pollinators, although T. laeviceps could act as a potential replacement or for the inundation of this service.